Epac1 and Glycyrrhizin Both Inhibit HMGB1 Levels to Reduce Diabetes-Induced Neuronal and Vascular Damage in the Mouse Retina - Liu, Li (J Clin Med, 2019)
The role of high mobility group box 1 (HMGB1) in acute diabetic retinal damage has been demonstrated. We recently reported that glycyrrhizin, a HMGB1 inhibitor, protected the diabetic retina against neuronal, vascular, and permeability changes. In this study, we wanted to investigate the role of exchange protein for cAMP 1 (Epac1) on HMGB1 and the actions of glycyrrhizin. Using endothelial cell specific knockout mice for Epac1, we made some mice diabetic using streptozotocin, and treated some with glycyrrhizin for up to 6 months. We measured permeability, neuronal, and vascular changes in the Epac1 floxed and knockout mice. We also investigated whether Epac1 and glycyrrhizin work synergistically to reduce the retinal inflammatory mediators, tumor necrosis factor alpha (TNFα) and interleukin-1-beta (IL1β), as well as sirtuin 1 (SIRT1) levels. Epac1 and glycyrrhizin reduced inflammatory mediators with synergistic actions. Glycyrrhizin also increased SIRT1 levels in the Epac1 mice. Overall, these studies demonstrate that glycyrrhizin and Epac1 can work together to protect the retina. Finally, glycyrrhizin may regulate HMGB1 through increased SIRT1 actions.